2008
DOI: 10.1124/dmd.108.022046
|View full text |Cite
|
Sign up to set email alerts
|

Substrate-Dependent Breast Cancer Resistance Protein (Bcrp1/Abcg2)-Mediated Interactions: Consideration of Multiple Binding Sites in in Vitro Assay Design

Abstract: ABSTRACT:In vitro assays are frequently used for the screening of substrates and inhibitors of transporter-mediated efflux. Examining directional flux across Madin-Darby canine kidney (MDCK) II cell monolayers that overexpress a transporter protein is particularly useful in identifying whether or not a candidate compound is an inhibitor or substrate for that transport system. Studies that use a single substrate or inhibitor in competition assays can be challenging to interpret because of the possible multiple … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(56 citation statements)
references
References 37 publications
1
54
0
1
Order By: Relevance
“…This was attributed to species differences of ABCG2. We observed a significant fold-increase in Pp-18 accumulation (comparable to inhibition by FTC or Ko143) in mouse and human ABCG2-expressing cell lines when adding the same concentrations of chrysin and benzoflavone used by Zhang et al Due to the existence of multiple binding sites on ABCG2 (Giri et al, 2009), there may be different transporter-mediated interactions, and competitive substrates may not inhibit the efflux of all transport substrates. As such, caution should be taken that an inhibitor of ABCG2 is dependent on the substrates tested.…”
Section: Functional Comparison Of Human and Murine Abcg2mentioning
confidence: 75%
“…This was attributed to species differences of ABCG2. We observed a significant fold-increase in Pp-18 accumulation (comparable to inhibition by FTC or Ko143) in mouse and human ABCG2-expressing cell lines when adding the same concentrations of chrysin and benzoflavone used by Zhang et al Due to the existence of multiple binding sites on ABCG2 (Giri et al, 2009), there may be different transporter-mediated interactions, and competitive substrates may not inhibit the efflux of all transport substrates. As such, caution should be taken that an inhibitor of ABCG2 is dependent on the substrates tested.…”
Section: Functional Comparison Of Human and Murine Abcg2mentioning
confidence: 75%
“…However, their ERs in M-BCRP cells were insensitive to Ko143. This can be due to differences in binding sites and substrate-dependent inhibition (Muenster et al, 2008;Giri et al, 2009). Those examples well illustrate that not only the ER value in M-BCRP cells should be taken into consideration, but the impact of Ko143 and the ER in the control cells to avoid falsenegative or false-positive results (Fig.…”
Section: Bcrp Substrate In Vitro Assaymentioning
confidence: 79%
“…Likewise, polarized transcellular assays are not suitable for low permeable compounds, since they do not sufficiently penetrate the cells and therefore do not reach the export protein, potentially resulting in false-negative results. The existence of multiple binding sites on transport proteins could also add to the complexity of identifying substrate and inhibitor molecules in in vitro assay systems, leading to incorrect interpretation (Muenster et al, 2008;Giri et al, 2009). Careful selection of substrates and inhibitors is therefore critical for designing definitive studies, and may circumvent the current issues with very high experimental interlaboratory variability in in vitro assays .…”
Section: Lowmentioning
confidence: 99%
“…In vitro assays showed that ABCG2 might have more than two binding sites, since ABCG2 inhibitors displayed different inhibition profiles, depending on the tested substrate [71][72][73] . For instance, the inhibitor Ko143 inhibited the transport of all the substrates tested by Giri et al [72] , which suggested its binding to a region that allosterically inhibits the transport of these substrates. However, the ABCG2 inhibitors elacridar, nelfinavir and Pluronic P85 seemed to bind to a different region, which inhibited the transport of the nucleoside analogs abacavir and zidovudine, but showed no or a partial effect on the transport of prazosin and imatinib.…”
Section: Breast Cancer Resistance Proteinmentioning
confidence: 99%
“…Examples are a wide range of anticancer drugs, sulfate and glucuronide conjugates of xenobiotics, tyrosine kinase inhibitors (TKIs), statins, fluorescent dyes and flavonoids [10,63] . In vitro assays showed that ABCG2 might have more than two binding sites, since ABCG2 inhibitors displayed different inhibition profiles, depending on the tested substrate [71][72][73] . For instance, the inhibitor Ko143 inhibited the transport of all the substrates tested by Giri et al [72] , which suggested its binding to a region that allosterically inhibits the transport of these substrates.…”
Section: Breast Cancer Resistance Proteinmentioning
confidence: 99%